2021
DOI: 10.18061/dsq.v41i3.8359
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of "remote working" in Covid-19 pandemic times: disability, inclusion, and accessibility in Brazil

Abstract: Due to the COVID-19 pandemic, many countries have adopted social isolation as a strategy to fight and limit the spread of the global crisis of Covid-19, which has impacted organization processes and employee's relationships with one another. Several issues such as the lack of accessibility and adaptations on work routines, that were already present in people with disabilities' life in the work environment are now highlighted, bringing to light theoretical debates and practical discussions about the experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Eight studies (four primary research [36,38,41,42], three perspective [43][44][45], one secondary analysis [46]) reported that the switch to working from home and other forms of virtual work improved accessibility for some workers with disabilities, such as spinal cord injury, Larsen Syndrome, anxiety disorders and autism. In Okyere et al's global survey of people with disabilities, the positive effects of working from home included increased control over work settings and a more supportive environment [41].…”
Section: Improved Accessibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies (four primary research [36,38,41,42], three perspective [43][44][45], one secondary analysis [46]) reported that the switch to working from home and other forms of virtual work improved accessibility for some workers with disabilities, such as spinal cord injury, Larsen Syndrome, anxiety disorders and autism. In Okyere et al's global survey of people with disabilities, the positive effects of working from home included increased control over work settings and a more supportive environment [41].…”
Section: Improved Accessibilitymentioning
confidence: 99%
“…Interestingly, Adams et al's study of individuals with spinal cord injury found that some individuals, who had already been working remotely prior to the pandemic but who had requested additional accommodations, finally had their requests granted once the pandemic began; however they did not specify the precise reason(s) for why these needs were now being met [36]. In another study, a professor with Larsen Syndrome explained that before the pandemic, he had (unsuccessfully) sought accessibility accommodations to teach remotely, because "being physically in the classroom was not always an option due to his conditions at that time" [42], (para.20). When the opportunity for remote work became a reality due to the pandemic, this represented the "first time he experienced supported employment" [42], (para.20).…”
Section: Improved Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations